Mycosins of the Mycobacterial Type VII ESX Secretion System: the Glue That Holds the Party Together - Jeffrey M. Chen (American Society for Microbiology, 2016)
ABSTRACT Since their discovery as important determinants of virulence and growth, the type VII ESX secretion systems (ESX-1 to ESX-5) of slow-growing pathogenic mycobacteria have been the focus of intense scrutiny. Genetic studies have been instrumental in identifying the core components and substrates of these molecular secretion machines and have helped uncover the multifunctional properties of some of them. For instance, the mycosin MycP1 of ESX-1, a membrane-associated subtilisin-like serine protease, was shown to have dual functions: the entire protein is essential for ESX-1 function, but only the serine protease regulates secretion activity. MycP5 of ESX-5, on the other hand, is required for ESX-5 secretion activity, but the function of its predicted serine protease remains unknown. Recently, van Winden and colleagues (mBio 7:e01471-16, 2016, http://dx.doi.org/10.1128/mBio.01471-16) reported compelling evidence that MycP1 and MycP5 serve to stabilize the interactions of core ESX-1 and ESX-5 components, respectively, thus explaining how they facilitate the secretion activities of their associated systems.